Konsep Teologi Calvinisme (Jurnal Pendidikan Agama dan Teologi, 2025)
This study is based on the urgency to understand Calvinism, one of the most influential theological systems in the history of Christianity, which originated from the thoughts of John Calvin in the 16th century. This theology emphasizes the sovereignty of God in the process of salvation, formulated in five core doctrines known by the acronym TULIP: Total Depravity, Unconditional Election, Limited Atonement, Irresistible Grace, and Perseverance of the Saints. The research adopts a qualitative descriptive approach using a library research method, aiming to explore the theological concept of Calvinism through the analysis of theological, historical, and doctrinal literature. The findings reveal that Calvinism forms a systematic theology of salvation that is entirely centered on God’s grace, without reliance on human effort. Additionally, the study highlights how Calvinist teachings have significantly influenced Christian life and church practices, both historically and in the present day. Therefore, it is important for these teachings to be understood and applied contextually in Indonesia, to remain relevant and avoid being misinterpreted as rigid or fatalistic doctrine.